2021
DOI: 10.1136/bmjopen-2020-043541
|View full text |Cite
|
Sign up to set email alerts
|

Urgent assessment and ongoing care for infection in community-dwelling older people: a qualitative study of patient experience

Abstract: ObjectivesTo explore the experience of infection from the perspective of community-dwelling older people, including access and preferences for place of care.DesignQualitative interview study, carried out between March 2017 and August 2018.SettingAmbulatory care units in Oxfordshire, UK.ParticipantsAdults >70 years with a clinical diagnosis of infection.MethodsSemistructured interviews based on a flexible topic guide. Participants were given the option to be interviewed with their caregiver. Thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These services have been shown to facilitate decision-making in the complex care required by older adults (Ploeg et al, 2019); for instance, they reduce the use of emergency services and high-cost hospitalization including potentially avoidable admissions (Lesser et al, 2020). The literature has revealed that OPPCSs also facilitate access to a number of community support services (Ploeg et al, 2019) that help them maintain optimal levels of autonomy (Moore et al, 2021, van de Pol et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These services have been shown to facilitate decision-making in the complex care required by older adults (Ploeg et al, 2019); for instance, they reduce the use of emergency services and high-cost hospitalization including potentially avoidable admissions (Lesser et al, 2020). The literature has revealed that OPPCSs also facilitate access to a number of community support services (Ploeg et al, 2019) that help them maintain optimal levels of autonomy (Moore et al, 2021, van de Pol et al, 2015).…”
Section: Introductionmentioning
confidence: 99%